The breastfeeding experiences of mothers with COVID-19 infection in a selected hospital, South India - Thurkkada, Anju Philip; Wilson, Namitha Sarah; Sajeev, Sathirshna Kovakkallil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Breastfeeding is the natural way of feeding a new-born. The COVID-19 scenario makes breastfeeding more challenging than usual periods. This study aimed to describe the breastfeeding experiences of mothers with COVID-19 infection. Qualitative data were collected from thirteen COVID-19-infected immediate postnatal mothers through google form questionnaires and in-depth interviews. The COVID-19 infected mothers faced difficulties in feeding their babies. Some of the mothers couldn’t be fed colostrum. Severe stress, lack of family and professional support, COVID-19 infection, and inadequate breastmilk production are the hindering factors affecting the breastfeeding habit of mothers. The main breastfeeding problems are apprehension of spreading the infection to the baby, physical separation due to COVID-19 infection, difficulty in latching, and reluctance to breastfeed after formula feeding. Even though there are lots of problems in breastfeeding among mothers and babies, breastfeeding must be initiated and maintained for the benefit of the mother and baby.